Development of a records and archives management program for the University of the Philippines (UP) School of Urban and Regional Planning (SURP) Library - Manjares, Maggie May I.; Olgado, Benedict S.; Lagrama, Eimee Rhea, C. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2018)
The UP SURP Library is encountering issues on records and archives management, including unsystematic records classification and organization, missing records (i.e. lost, misfiled, and unlocated records), inefficient records and archives access and retrieval, some archives have already been categorized by type but majority are not. Some have not yet been classified, accessioned, cataloged, labeled nor inventoried yet. The library does not have any written tools and manual on records and archives management. This project will fill that gap by developing a records and archives management program (RAMP) for the UP SURP Library. Having RAMP leads to effective delivery of services and efficient office operations because it guides the Library in collecting, assessing, describing, organizing and preserving institutional/community knowledge and history.
The outputs of this project which include the tools such as records classification schedule, RRDS and a manual. These may be used by the other libraries or offices with the similar undertaking. As a proof, this project's positive impact on Library's efficient retrieval of records and archives, three instances have been recorded: (1) the library was able to submit the electronic accession inventory list (AIL) of purchased book before the set deadline by the UP University Library; (2) the Library was able to provide the photographs of the founding dean for the AV presentation for his necrological service; (3) the Library discovered the presence of a library faculty committee back in the 1970s. These situations thereby strengthen the need for RAMP in every institution.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: School of Urban and Regional Planning (SURP) Library -- University of the Philippines -- Diliman; Records and archives management; Records management